Parámetros biométricos del segmento anterior en pacientes con síndrome pseudoexfoliativo del Instituto Regional de Oftalmología - Pretel Mostacero, Olinda Cecilia (2019)
Purpose: To characterize the anterior segment of patients with pseudoexfoliation syndrome and healthy controls through Scheimpflug tomography. Methods: Cross-sectional and prospective study in patients with pseudoexfoliation syndrome seen at Instituto Regional de Oftalmología - Javier Servat Univazo (IRO-JSU) from August 1, 2017 to April 30, 2019. We included patients > 60 years of age, both sexes, with some degree of pseudoexfoliation (pupillary, angular, capsular), axial length of 22-25 mm and degree of nuclear opacity (2-4 LOCS III). Keratometries, corneal thickness, corneal density, depth and angle of the anterior chamber were measured by Scheimpflug tomography. These parameters were compared with those of the control group (matched by age and degree of nuclear opacity) through the one-way ANOVA test. Results: 31 eyes of 31 patients with pseudoexfoliation syndrome (4/31 with glaucoma) and 31 eyes of 31 controls. Corneal density was higher in patients with pseudoexfoliation syndrome than in controls (19.78 ± 2.03 GSU and 17.46 ± 1.84 GSU, respectively, p = 0.000). There were no statistically significant differences in keratometry, corneal thickness, depth and angle of anterior chamber angle between both groups. In the pseudoexfoliation group, patients suffering of glaucoma had a clinically lower corneal thickness than those without it (504.7 vs. 531.1, p = 0.237). Conclusions: Pseudoexfoliation syndrome is associated with an increase in corneal density measured by Scheimpflug tomography. In this group of patients, corneal thickness was clinically lower for those with glaucoma.